2012
DOI: 10.1097/aln.0b013e31825685a6
|View full text |Cite
|
Sign up to set email alerts
|

Azd-3043

Abstract: Background Propofol can be associated with delayed awakening after prolonged infusion. The aim of this study was to characterize the preclinical pharmacology of AZD-3043, a positive allosteric modulator of the γ-aminobutyric acidA (GABAA) receptor containing a metabolically-labile ester moiety. We postulated that its metabolic pathway would result in a short acting clinical profile. Methods The effects of AZD-3043, propofol and propanidid were studied on GABAA receptor-mediated chloride currents in embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The effect of AZD3043 on nAChR has not been investigated before [ 14 ], but is more potent in inhibition of the adult muscle nAChR compared to propofol. AZD3043 shares the same properties as propofol in terms of inhibition of the α3β2 nAChR subtype, but lacks the positive modulation of the α7 subtype seen with propofol although the IC 50 values were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of AZD3043 on nAChR has not been investigated before [ 14 ], but is more potent in inhibition of the adult muscle nAChR compared to propofol. AZD3043 shares the same properties as propofol in terms of inhibition of the α3β2 nAChR subtype, but lacks the positive modulation of the α7 subtype seen with propofol although the IC 50 values were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Flood and co-workers have previously demonstrated that propofol has a low sensitivity for the α7 nAChR subtype but it has not been investigated whether propofol interacts with the adult α1β1δε subtype or the presynaptic α3β2 nAChR subtype. AZD3043 is a new rapid acting intravenous anesthetic agent currently in clinical trials and with similar effects as propofol on the GABA A receptor, but the affinity for other receptor types has not been investigated in detail [ 13 , 14 ]. Thus, it has not been investigated whether AZD3043 inhibits nAChRs in the NMJ or how much muscle relaxation ADZ3043-based anesthesia provides.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum potentiation achieved by compound 5j (EC 50  = 12.0 µM) was approximately 50% of that produced by propofol (EC 50  = 2.4 µM) and 150% of that of propanidid (EC 50  = 25.2 µM) (Figure 7) (EC 50 value of AZD3043 was 36 µM [6]). …”
Section: Resultsmentioning
confidence: 99%
“…6.5.6. Hypnosis in response to intravenous (IV) infusion [19] Induction of hypnosis in rats were achieved using 2 Â HD 50 dose of test compound, and immediately after induction, infusion via the tail vein was commenced at HD 50 dosage per min. the infusion rate was maintained for 20 min or 1 h or 3 h later.…”
Section: Therapeutic Index (Ti)mentioning
confidence: 99%